Streptomyces species producing the streptovaricin complex - Vesselinova, N; Gesheva, R; Ivanova, V (Folia microbiologica, 1991)
Morphological, cultural and physiological-biochemical properties of Streptomyces sp. strain 1000 and its antibiotic production were investigated. Antibiotics 1011 (identical with the streptovaricin complex) and 1012 (with antibacterial action) were isolated from the cultural broth of this strain. The overproducing natural variant 1011 was isolated from the population of a strain producing antibiotic 1011 at a concentration of 1000 mg/L (activity of the parent strain represents 41 mg/L only). Comparative taxonomical characteristic of Streptomyces sp. strain 1000 with strains from S. spectabilis showed that the strain 1000 differed in some properties and antibiotic production being considered as a new variant of S. spectabilis. The strain shows an expressed antibiotic activity against G+ as well as G- bacterial and yeasts.
Keywords: druhová specificita; Streptovaricin; Species Specificity; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; Streptomyces; streptovariciny